India's emerging nuclear posture : between recessed deterrent and ready arsenal - Tellis, Ashley J. (Rand, 2000)
On May 11, 1998, after a hiatus of more than two decades, India conducted a series of nuclear tests that signaled a critical shift in its strategic thinking. Once content to embrace a nuclear posture consisting largely of "maintaining the option"--I.e., neither creating a nuclear arsenal nor renouncing its right to do so--India is now on the threshold of adopting a posture that, while stopping short of creating a ready arsenal, will take as its goal the establishment of a "minimum but credible deterrent, " known as a "force-in-being." This book examines the forces--political, strategic, technological, and ideational--that led to this dramatic policy shift and describes how New Delhi's force-in-being will be fashioned, particularly in light of the threat India faces from its two most salient adversaries, China and Pakistan. The book evaluates in detail the material, infrastructural, and procedural capabilities India currently possesses as well as those it is likely to acquire in its efforts to meet the needs of its evolving force-in-being. Finally, the volume concludes by assessing the strategic implications of India's posture both on the South Asian region in particular and on the global nonproliferation regime in general